The Multiplier Effect of Portfolio Investment on Economic Growth in Indonesia: A Case for the Manufacturing and Financial Sectors 2010–2020 - Zhaditya Pradana Putra Mars; FX Sugiyanto (Diponegoro Journal of Economics, 2024)
This research aims to understand how the multiplier effect of portfolio investment affects economic growth in Indonesia. Using a panel Fixed Effects Model analysis with quarterly data ranging from 2010 to 2020, the findings suggest that the portfolio investment multiplier effect positively influences economic growth. However, its overall impact is lower than the estimation, and only the manufacturing sector has a meaningful impact on economic growth.